Stakeholders’ rank of reflexion diagnostics in a corporate social responsibility system - Kamyshnykova, E. V.; Mints, A. Yu.; Schumann, А.; Мінц, О. Ю. (Institute of Society Transformation, 2020)
The use of new methods and technologies for managing relations with stakeholders in a corporate social responsibility system, in particular the reflexive approach, forms the basis for increasing the effectiveness of socially responsible management. The category of «rank of reflexion» occupies a significant place in the methodology of reflexive management modelling. Reliable diagnostics of the stakeholders’ rank of reflexion is one of the important areas increasing the efficiency of socially responsible decisions and actions in the process of reflexive management. The purpose of this paper is to substantiate the use of the fuzzy-logic method for diagnostics of the stakeholders’ rank of reflexion and formulate types of reflexive management of corporate social responsibility depending on the rank and level of complexity. The authors substantiate that when applying methods of reflexive management in practice, in the long run, the ambiguity and variability of the stakeholders’ rank of reflexion have to be taken into account. This corresponds to the system’s properties of dynamism (B1), adaptability (B2) and structure (B3). Given that the existing apparatus of reflexive management takes into account mainly one-time influences, the article suggests using the fuzzy diagnostic method to determine the stakeholders’ rank of reflexion. There is a case showing formulation and solution of the problem of determining the stakeholders’ rank of reflexion by using mathematical fuzzy logic. It is proved that the storage of the estimates of the stakeholders’ reaction as fuzzy sets allows considering the conclusion of B3, giving opportunities for further analysis of patterns changing the stakeholder’s rank of reflexion within the conclusions B1 and B2. The results of the study show that the rank of reflexion increasing in the company promotes corporate social responsibility growth through a more effective interaction with the stakeholders. Five types of reflexive management of corporate social responsibility are proposed depending on the rank and complexity level of reflexion, used by the company’s management, namely: defensive, compliance, managerial, strategic, and civil. The use of relevant reflexive influences as implementation tools of corporate social responsibility provides increasing efficiency of interaction with stakeholders. The prospects of the follow-up research on this topic should include the classification of the company’s reflexive influences on the stakeholders.
Keywords: Corporate Social Responsibility; Stakeholder; Rank of Reflexion; Reflexive Management; Reflexive Games; Fuzzy Logic